2019
DOI: 10.1002/1878-0261.12567
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of HECT‐type E3 ubiquitin ligases in autophagy regulation

Abstract: Autophagy is a conserved self‐eating process that delivers cytoplasmic material to the lysosome to allow degradation of intracellular components, including soluble, unfolded and aggregated proteins, damaged organelles, and invading microorganisms. Autophagy provides a homeostatic control mechanism and is essential for balancing sources of energy in response to nutrient stress. Autophagic dysfunction or dysregulation has been implicated in several human pathologies, including cancer and neurodegeneration, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…At the same time, p63 contributes to the stemness phenotype through its ability to bind to promoters of several components of the Sonic Hedgehog (Hh) signalling pathway and its three ligands-Sonic (SHH), Desert, and Indian (IHH)-and to the Patched (PTCH) receptors that inhibit the G-coupled transmembrane protein Smoothened (SMO); in turn, GLI proteins become transcriptional activators (GLI A ) and induce the expression of Hh target genes, including those involved in stem cell regulation (for example, Bmi1) [69,79]. In this manner, p63 regulates the stemness compartment in breast cancer [69], while inhibiting cell death [80]-a process regulated by p63-triggered proteasomal degradation [81][82][83][84]. Additional mechanisms involving p63 and tumour progression have been evoked in breast cancer [85,86], as well as for other tumours [87,88].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, p63 contributes to the stemness phenotype through its ability to bind to promoters of several components of the Sonic Hedgehog (Hh) signalling pathway and its three ligands-Sonic (SHH), Desert, and Indian (IHH)-and to the Patched (PTCH) receptors that inhibit the G-coupled transmembrane protein Smoothened (SMO); in turn, GLI proteins become transcriptional activators (GLI A ) and induce the expression of Hh target genes, including those involved in stem cell regulation (for example, Bmi1) [69,79]. In this manner, p63 regulates the stemness compartment in breast cancer [69], while inhibiting cell death [80]-a process regulated by p63-triggered proteasomal degradation [81][82][83][84]. Additional mechanisms involving p63 and tumour progression have been evoked in breast cancer [85,86], as well as for other tumours [87,88].…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that the HECT gene family influences ATP binding, isopeptidase activity, histone binding, protease activity, and numerous molecular and biological processes in tomato. The HECT E3 ubiquitin ligases have been identified to regulate trichome development 54 , leaf senescence 55 , biotic stress 56 , cell growth, proliferation, autophagy, DNA repair, antiviral responses, and many diseases 40 . Our results agree with previous studies and predict extended involvement in the tomato cellular and genetic processes.…”
Section: Discussionmentioning
confidence: 99%
“…HUWE1 is an E3 ubiquitin ligase harboring HECT domain, which is known to regulate cell proliferation and cell death and, thus, is potentially an important factor in tumorigenesis [33][34][35][36]. However, functional studies have reported discordant effects of changes in HUWE1 activity due to its functionally diverse targets.…”
Section: Discussionmentioning
confidence: 99%